Growth Response of Lime (Citrus aurantifolia Swingle) cutting on various plant materials and IBA (Indole Butyric Acid) Concentrations - lia agnes lumban gaol; meiriani meiriani (Jurnal Agroekoteknologi, 2016)
The objectives of the research was to determine the responses of different type of lime cutting as plant materials and IBA concentrations on growth was carried out at field trial of Agriculture Faculty, University of North Sumatera, Medan (± 25 m asl) on June – September 2015 with used factorial Randomized Block Design (RBD) with two factors were plant materials (shoot cutting without leaves; stem cutting with leaves; and stem cutting without leaves) and IBA concentrations (0; 100; 200; and 300 ppm) and three replications. The result showed that the growth of lime shoot cutting without leaves significantly better than the other treatments and the aplication of 300 ppm IBA concentration significantly increased 44,05 % shoot length than without IBA. There was no significant interaction between the plant material used and the aplication of IBA concentrations for all parameters observed.